2012
DOI: 10.1002/ceat.201200269
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of a Solar Reactor for Phenol Treatment by the Photo‐Fenton process in Aqueous Solution

Abstract: Solar reactors can be attractive in photodegradation processes due to lower electrical energy demand. The performance of a solar reactor for two flow configurations, i.e., plug flow and mixed flow, is compared based on experimental results with a pilot‐scale solar reactor. Aqueous solutions of phenol were used as a model for industrial wastewater containing organic contaminants. Batch experiments were carried out under clear sky, resulting in removal rates in the range of 96–100 %. The dissolved organic carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 32 publications
1
2
0
1
Order By: Relevance
“…Executing the process at initial pH of 10.2 led to decrease the degradation efficiency to 80 % after 90 min of light irradiation. This result could be due to low rate of decomposition of H 2 O 2 at pH exceeding 4.0 which resulted in a drop of production of hydroxyl radicals (Li et al 2009 dosage effect is close to the reported results in other works with some discrepancies in the dosage values according to the initial concentration of phenol and the reaction conditions (Yavuz et al 2007;Zazo et al 2009;Pontes et al 2010;Nogueira et al 2012).…”
Section: Effect Of Initial Phsupporting
confidence: 87%
See 1 more Smart Citation
“…Executing the process at initial pH of 10.2 led to decrease the degradation efficiency to 80 % after 90 min of light irradiation. This result could be due to low rate of decomposition of H 2 O 2 at pH exceeding 4.0 which resulted in a drop of production of hydroxyl radicals (Li et al 2009 dosage effect is close to the reported results in other works with some discrepancies in the dosage values according to the initial concentration of phenol and the reaction conditions (Yavuz et al 2007;Zazo et al 2009;Pontes et al 2010;Nogueira et al 2012).…”
Section: Effect Of Initial Phsupporting
confidence: 87%
“…According to the light sensitivity of the photo-Fenton reaction with respect to the solar spectrum, the utilization of a solar light source is considered to be very economic alternative as compared to UV lamps for treatment of wastewater at a full scale (Nogueira et al 2012;Luna et al 2013). Many researchers reported that compound parabolic collectors (CPC) technology is suitable for application of solar photo-Fenton process (Lafi and Al-Qodah 2006;Vilar et al 2011;Souza et al 2013) because UV light is reflected and intensified towards the solution moving in the reactor tubes (Gar Alalm et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, optimal values are chosen to obtain higher deterioration at lower costs (Ahmad et al 2019;Radwan et al 2019). H 2 O 2 did not influence the breakdown of agrochemical wastewater using photo-Fenton at low concentrations (10-50 mmol/L), while the effects clearly increased at larger concentrations of H 2 O 2 , such as 500 mmol/L (Nogueira et al 2012). Many researchers discovered that increasing the amount of iron salt in the solution increased the rate of contaminant degradation until it reached the optimum dose, after which the rate of degradation decreased (Miralles-Cuevas et al 2021;Soriano-Molina et al 2021c;Vilela et al 2021).…”
Section: Fenton Reagent Dosagementioning
confidence: 99%
“…As reações que envolvem o processo estão listadas abaixo. (Pignatello et al, 2006, Nogueira et al, 2012.…”
Section: Processos Fenton E Foto-fentonunclassified